Pelaksanaan Metode Demonstrasi pada Pelatihan â€œKreativitas Menjahitâ€ di UKM Kota Padang Provinsi Sumatera Barat - Pratama, Buktika Syahril; Jamna, Jamaris (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research is motivated by the high activity of sewing creativity trainees in UKM Padang, West Sumatra. This is allegedly due to the use of the learning methods used by the instructor in the training. This study aims to: describe the form of preparation, implementation and evaluation of the sewing creativity training process in UKM City of Padang, West Sumatra, using Demonstration learning methods. This research is a correlational quantitative study. The population in this study were all sewing creativity training participants in UKM Kota Padang, West Sumatra. The sampling technique is cluster random sapling. The data collection technique used was a questionnaire, while the data collection tool used a questionnaire in the form of a list of questions distributed to trainees. Data analysis techniques use percentages. The results of this study indicate that based on aspects such as preparation, implementation, evaluation in the use of demonstration methods in sewing creativity training in SMEs in Padang, West Sumatra. This is evidenced by the large number of trainees choosing alternative answers SR (Frequently) and SL (Always) in each of these aspects. Suggestions in this study are: it is expected that the use of learning methods in training is interesting and not tedious and can increase the activity and participation of students in the learning process, so that the process of acceptance of learning can be conveyed properly. And it is hoped that the use of demonstration learning methods by instructors can be maintained in every training that is carriedout.